ELTV Week-in-Review (African Knowledges and the History Publication since the 1970s)
President Samuel Kanyon Doe addresses the public on world politics (South Africa, Palestine, Lebanon, Iran, Iraq, etc.) and international relations; various news from Liberia, including an agricultural workshop, relations with Niger, and the inauguration of a new health ministry building; includes advertisement breaks.
Keywords: Public relations; News; Politics